The essence and structure of information and communication pedagogical environment - Онищенко, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Onishchenko I. V. The essence and structure of information and communication pedagogical environment. The article reveals the essence of information and communication pedagogical environment, defined by its role in the training of future teachers. The opinion that the information and communication environment is a complex pedagogical educational system, which includes the information, organizational, intellectual, methodological, technical, program resources that increase efficiency and the quality of specialists’ training.